The Protection of Journalists in Armed Conflicts: How Can They Be Better Safeguarded? - Düsterhöft, Isabel (Utrecht Journal of International and European Law, 2013)
The years 2011 and 2012 were among the most deadly for journalists reporting from conflict situations worldwide. The numbers of assaults, arrests and attacks have been on a constant rise and portray a dramatic image of the journalistic profession. In light of the increasing threats in armed conflicts, being a war reporter has become an inherently dangerous task. Journalists are not only at risk of becoming so-called collateral damage during military operations, they are also increasingly targeted. Their role as a watchdog and witness to the horrors of war, in addition to the undeniable power of the word and image they spread, has made them popular targets. It is therefore essential that the international community re-evaluate journalists' de jure and de facto protections in armed conflicts to allow for better safeguards and consequently less casualties in the imminent future. This article examines the current protections afforded to journalists and aims at detecting proposals for enhanced safeguards that are most likely to effectively improve journalists' safety in the field. In this regard, this article will argue that the legal protections are in fact sufficient and hardly amendable and that therefore, a more practical, hands-on approach to implementation of those protections must be the focus of future actions. This goal can only be achieved by a comprehensive mission jointly pursued by governments, militaries, journalists, media, NGOs and society.